Geomorfologia e paleo-hidrologia dos megaleques dos rios Cuiabá e São Lourenço, quaternário da Bacia do Pantanal - Pupim, Fabiano do Nascimento [UNESP] (2014)
The Upper Paraguay River Basin (BAP) comprises three areas with remarkable different conditions regarding to physical and biological aspects: the plateaus, lowlands and plains of the Pantanal. The Pantanal dynamics depends directly on the interactions with the surroundings depressions and plateaus. Considering the peculiarities and environmental importance of the area, the goals of this study were to investigate aspects of the Quaternary evolution of fluvial megafans formed by the Cuiabá and São Lourenço rivers in the northern portion of the Pantanal, as well the degradational systems of the Cuiabana Depression in the source area. Remote sensing, sedimentological and geochronological data were used to achieve these goals. Satellite images and digital elevation models were used in geomorphological zoning and channel patterns analysis. Facies analysis and optically stimulated luminescence dating (OSL) allowed the characterization of depositional environments and establishment of the depositional events chronology. Cosmogenic nuclide analysis (10Be) enabled the determination of erosion rates and exposure ages in the Cuiabana Depression terrains. The results obtained showed that: 1) the depositional systems formed by Cuiabá and São Lourenço rivers were built during the Late Quaternary and may be classified as fluvial megafans; 2) the megafans consist in Pleistocene lobes with paleochannels with braided patterns and Holocene lobes created by meandering and distributaries channels; 3) the confined floodplains in the upper portions of the megafans truncate ancient lobes' surface, configuring incised valleys; 4) based on OSL ages, the shift from braided to meandering pattern occurred in a time interval between the Last Glacial Maximum and the Early Holocene, being an example of tropical river systems response to global climate changes; 5) 10Be cosmogenic erosion rates show us that the relief evolution of the Cuiabana Depression have strong...